Severe Acute Liver Injury Related to Heat Stroke - Ribeiro, F (2020)
Heat stroke (HS) is a life-threatening condition characterized by hyperthermia and multiple organ failure. Mild to moderate hepatocellular injury is a well-documented complication but severe liver injury and acute liver failure are rare. There are neither established criteria nor optimal timing for liver transplantation and conservative management seems to be the cornerstone treatment. The authors report a case of a patient with severe liver injury related to HS who recovered completely under conservative treatment. Learning points: Hyperthermia, neurologic dysfunction and recent exposure to hot weather or physical exertion should raise the suspicion of heat stroke (HS).Fast and effective cooling is the cornerstone of treatment, along with support of organ dysfunction. Antipyretics have no role in HS management.Conservative treatment has been described as being successful in the management of patients with HS that manifest severe acute liver injury (ALI) and acute liver failure (ALF). However, early referral to a liver transplantation centre is essential to guide treatment.